Why Should We Care About Care? The Role of Childcare and Eldercare in Armenia - World Bank (World Bank, Washington, DC, 2019)
Only 56 percent of women ages 15-64 participate in the labor market, a slightly higher share than the Europe and Central Asia average, but 18 percentage points lower than the share among men in Armenia. The conflicting demand on women's time for care and work activities represents a fundamental barrier to economic participation and generates a vicious circle of low labor market attachment and prominence of the care provider role that leads to increased vulnerability and gender-based inequalities. International evidence shows that support for childcare and eldercare affects women's labor market participation. This note examines the care needs of families with children and/or elderly household members and the provision of formal care services in Armenia with an emphasis on the availability, price, and quality characteristics. Based on the analysis of an independent mixed-methods dataset collected in several countries of Europe and Central Asia, this note documents the perceptions and barriers in the use of quality formal care in Armenia. Five main messages emerge from the assessment of supply and demand of formal childcare and eldercare in Armenia: 1) Although social norms strongly highlight the role of women as caregiver, there is scope for policy aimed at increasing access and affordability of childcare and early education: Around 24 percent of parents of children ages 0 to 5 currently not attending kindergarten report that the reason of no attendance is lack of the service or being unable to afford it. 2) The demand for childcare services is voiced predominantly by parents perceiving benefits for their child’s development and working (or willing-to-work) mothers. 3) Use of childcare is regressive: There are significant differences in enrollment to kindergarten and nursery between the poorest and the richest households (12.7 and 36.4 percent respectively). A well-developed childcare sector not only would help generating economic participation opportunities for women but also implies potential improvements in the school readiness for children especially for the most vulnerable households. 4) Day-care centers and home-based formats—if available—will be more compatible with prevailing standards of care for the elderly. 5) Quality is important for potential users of formal care services and the main challenges of the existing supply involves human resources (HR).